Inorganic sulfur cycles in sediments of the Pearl River Estuary: Processes, mechanisms, and isotopic indicators. (5th January 2023) - Yin, Xijie; Lin, Yunpeng; Li, Yunhai; Wang, Liang; Sun, Zhilei; Li, Guogang
Abstract: The burial of inorganic sulfur is one of the important components in the global sulfur cycle. In this study, the cycling of inorganic sulfide species and the underlying control mechanisms were examined in sediments found in distinct sub-regions of the Pearl River Estuary (PRE). Specifically, the content and isotopic composition of SO4 2−, acid-volatile sulfides (AVS), and pyrite were determined, along with sedimentary sulfate reduction rates (SRR). The results show that the formation of iron sulfides (such as AVS and pyrite) was mainly controlled by the content of available reactive iron in the sediments of the PRE, and therefore formed mainly in the shallow sediments, with little variation in the deeper parts of the sediments. The δ 34 S values of AVS and SO4 2− increased synchronously with depth in the middle and lower part of the sediment, indicating a closed diagenetic environment. In contrast, the δ 34 S value of pyrite only increased slowly with depth in the case of a small portion of AVS converted to pyrite, which was controlled by the burial time. There are obvious differences in the formation and burial of pyrite in sediments of different sub-regions of the PRE. The surface layer of stations QA and HQ in the upper estuary and brackish coast was an open environment due to sedimentary reworking, and the contents of AVS and pyrite in the sediment was extremely low due to re-oxidation, while the oxidation of 32 S-rich H2 S also resulted in lower δ 34 S values of sulfate in the sediment pore water than in the overlying seawater. Station GS in the estuarine mouth had a much higher percentage of AVS converted to pyrite in the sediments than that at stations QA and HQ due to the relatively long burial time. In addition, near the sulfate methane transition zone (SMT), only the estuarine mouth (station GS) produced iron sulfides (AVS) synchronously with the anaerobic oxidation of methane (AOM), and then converted to pyrite gradually; in contrast, the effect of AOM on the formation of iron sulfides in the sediments of the upper estuary and the brackish coast was almost negligible. The results show that the contribution of AOM processes to the final burial of inorganic sulfur is generally small in PRE. Highlights: Pyrite formation is mainly controlled by the content of available reactive iron in sediment. The conversion of AVS to pyrite occurred slowly in the deep sediment. Differences in the formation and burial of pyrite exist in different sub-deposit environments. The effect of AOM on the formation of pyrite was almost negligible.